Understanding the Transition from Perception to Action: A Path Analysis of Students’ Perceptions of Science and Their Intention to Act in Learning - Desi Eka Nur Fitriana; Nabilah Artanti; Nurhasanah Nurhasanah; Nasya Zaida Aziz; Siti Aisyah; Alya Muna Zhafirah; Siti Ajha; Suhendar Suhendar (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Students' perceptions of science were not only a response, but this is one of the factors that influence the motivational process and the formation of intention to act. This study aimed to analyze the causal relationship between students' perceptions of science learning and their intention to act in learning. The research method used is a survey method (exposure facto) using path analysis. The research instrument used was a questionnaire. The questionnaire statements consist of positive and negative statements measured using likert scale with five response categories. The subjects in this study were students of at a Private Senior High School in Serang, Indonesia with a total of 76 respondents. The results of the study indicate an influence of students' perceptions of science on their intention to act in learning with a path coefficient of p21 = 0.805. These results can be a basis for strengthening teachers in designing learning.